CARBON MITIGATION STRATEGY WITH ENGINEERED TIMBER: THE CASE OF MJØSTÅRNET - Rafaela Evanesse Paembonan; Eunike Kristi Julistiono (Jurnal Arsitektur ARCADE, 2026)
Abstract: Mjøstårnet is a building that applies sustainable construction principles throughout its lifecycle, with timber as the primary building material. The use of timber, particularly locally-sourced and prefabricated timber, contributes to improved environmental performance by reducing transportation-related emissions, minimizing construction waste, and offering carbon storage potential during its service life. This research aims to explore opportunities to further reduce embodied carbon in the building by proposing alternative material scenarios. The study employs an embodied carbon assessment focusing on slab construction, which represents one of the largest contributors to upfront embodied carbon in the building. Alternative scenarios include replacing slab materials with cross-laminated timber (CLT) and fly ash concrete with varying substitution levels. The results indicate that replacing conventional slab materials with CLT can reduce embodied carbon by 25.59%, while the use of fly ash concrete with a 40% replacement level achieves a reduction of 14.07%. The combined application of these strategies demonstrates a potential embodied carbon reduction ranging from 29.47% to 39.81%. These findings confirm that material substitution, particularly in slab construction, is an effective strategy for mitigating embodied carbon in sustainable building design. Keyword: Embodied Carbon, Timber Construction, Sustainable Construction Technology Abstrak: Mjøstårnet merupakan bangunan yang menerapkan prinsip konstruksi berkelanjutan selama umur bangunan, dengan kayu sebagai material utama. Penggunaan kayu, khususnya kayu lokal dan prefabrikasi, berkontribusi pada pengurangan emisi karbon melalui potensi penyimpanan karbon, efisiensi transportasi, penghematan energi, serta minimisasi limbah konstruksi. Penelitian ini bertujuan untuk mengevaluasi peluang peningkatan kinerja keberlanjutan bangunan melalui pengurangan embodied carbon, dengan fokus pada elemen struktur yang memiliki kontribusi karbon terbesar, yaitu plat lantai. Metode penelitian dilakukan melalui perhitungan embodied carbon pada beberapa skenario alternatif material, meliputi penggantian pelat lantai dengan cross-laminated timber (CLT) dan beton fly ash dengan variasi kandungan. Hasil penelitian menunjukkan bahwa penggunaan CLT mampu menurunkan embodied carbon sebesar 25,59%, sementara penggunaan beton fly ash dengan kandungan 40% menghasilkan penurunan sebesar 14,07%. Kombinasi kedua strategi tersebut berpotensi mereduksi embodied carbon antara 29,47% hingga 39,81%. Temuan ini menegaskan efektivitas pemilihan material sebagai strategi mitigasi embodied carbon pada bangunan berkelanjutan. Kata Kunci: Emisi Karbon, Konstruksi Kayu, Teknologi Konstruksi Kayu